Postoperative feeding in neonatal duodenal obstruction - Dolrudee Aroonsaeng; Paul D. Losty; Pornsri Thanachatchairattana (BMC, 2022)
Abstract Background Findings from manometry studies and contrast imaging reveal functioning gastric physiology in newborns with duodenal atresia and stenosis. Stomach reservoir function should therefore be valuable in aiding the postoperative phase of gastric feeding. The aim of this study was therefore to compare the feasibility of initiating oral or large volume(s) gavage feeds vs small volume bolus feeds following operation for congenital duodenal anomalies. Methods Single-center electronic medical records of all babies with duodenal atresia and stenosis admitted to a university surgical center during January 1997-September 2021 were analyzed. A fast-fed group (FF) included newborns fed with oral or gavage feeds advanced at a rate of at least 2.5 ml/kg and then progressed more than once a day vs slow-fed group (SF) fed with gavage feeds at incremental rate less than 2.5 ml/kg/day for each time period of oral tolerance or by drip feeds. Total feed volume was limited to 120-150 ml/kg/day in the respective study cohort populations. Results Fifty-one eligible patients were recruited in the study - twenty-six in FF group and twenty-five in SF group. Statistically significant differences were observed in the (i) date of first oral feeds (POD 7.7 ± 3.2 vs 16.1 ± 7.7: p < 0.001), and (ii) first full feeds (POD 12.5 ± 5.3 vs 18.8 ± 9.7: p < 0.01) in FF vs SF study groups. Conclusion Initial feeding schedules with oral or incremental gavage-fed rates of at least 2.5 ml/kg in stepwise increments and multi-steps per day is wholly feasible in the postoperative feeding regimens of neonates with congenital duodenal disorders. Significant health benefits are thus achievable in these infants allowing an earlier time to acquiring full enteral feeding and their hospital discharge.